Women as the Essential Protectors of Children?: Gender and Child Protection in UN Peacekeeping. Issue 2 (15th March 2022) - Johnson, Dustin
ABSTRACT: The United Nations and many member states have placed increased emphasis on improving child protection in UN peacekeeping missions, particularly with regard to child soldiers. These efforts often depict a critical role for female peacekeepers in child protection. In this paper I analyse UN child protection documents, drawing on feminist critiques of gendered discourses in peacekeeping and work on children in global politics to explore how the UN understands gender in child protection contexts. I do so through an analysis of how peacekeepers' gendered subject positions and representations of children in need of protection are constructed. I find that the construction of children primarily as victims lacking agency and in need of being saved, and a focus on female peacekeepers primarily in community engagement, risk perpetuating the neglect of children's agency during armed conflict and leave the protective masculine basis of peacekeeping largely unchallenged. These constructions have implications for the implementation of both the children and armed conflict and WPS agendas in peacekeeping.